2006
DOI: 10.1103/physrevc.73.044316
|View full text |Cite
|
Sign up to set email alerts
|

Half-life measurements of several states inSr95,97,Zr97,100,

Abstract: Half-lives T 1/2 of states in 95,97 Sr, 97,100,104 Zr, 106 Mo, and 148 Ce, which decay by delayed γ transitions, were determined by using a new time-gated triple γ coincidence method. Transition energy dependent effects such as time walks, time jitters, amplitude walks, and possible timing fluctuations of Ge detectors that contribute to the width of the time window were taken into consideration by comparing prompt and delayed cascades with similar transition energies. It is shown that the normalized triple γ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 17 publications
3
22
0
Order By: Relevance
“…2a which cannot be explained with such simple considerations. havior may be due to the fact that Zr isotopes (Z = 40) in the mass range 100 − 112 are strongly bound with a large prolate deformation around β 2 = 0.42 [48][49][50]. Due to shell effects, these configurations may be energetically favorable during the QF dynamics [16,17,19].…”
Section: Pb Targets Ormentioning
confidence: 99%
“…2a which cannot be explained with such simple considerations. havior may be due to the fact that Zr isotopes (Z = 40) in the mass range 100 − 112 are strongly bound with a large prolate deformation around β 2 = 0.42 [48][49][50]. Due to shell effects, these configurations may be energetically favorable during the QF dynamics [16,17,19].…”
Section: Pb Targets Ormentioning
confidence: 99%
“…A large set of experimental data (charge radii [69], rotational bands [73] and B(E2) values [74]) demonstrate that 100 Zr is located in a region of deformed nuclei. An excited band built on a 0 + state coexisting with the ground-state band [73], and the large E0 transition strength between the 0 + states [75] indicate the coexistence of shapes with different deformations, the state with the largest deformation being the ground state.…”
Section: Zrmentioning
confidence: 99%
“…By including the β 30 deformation, a pear-like ground state of 112 Zr is predicted with the functional DD-PC1 [21]. From the experimental point of view, the analysis of rotational bands, β-decay half-lives, and lifetimes of the first 2 + states reveals that some of these nuclei are well deformed [62,[152][153][154][155][156][157][158][159][160][161][162][163][164] Next we give some numerical details and illustrative calculations of the MDC-RHB model. Then we present and discuss the results for neutron-rich even-even Zr isotopes calculated with functionals DD-PC1 [111] and PC-PK1 [166].…”
Section: Resultsmentioning
confidence: 99%
“…Several experiments were devoted to the study of tetrahedral shapes in 160 Yb [58], 154,156 Gd, although the observed odd and even-spin members of the lowest energy negative-parity bands are similar to the proposed tetrahedral band of 156 Gd, the deduced nonzero quadrupole moments existence of tetrahedral shapes in these nuclei. The possibility of a tetrahedral shape for the negative-parity bands in 230,232 U was excluded in Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation